Valoración microbiológica en superficies inertes en el camal Municipal de Quevedo, 2019 - Vásquez Acosta, Johanna Nathaly (2019)
This research work aims to know the presence or absence of pathogenic microorganisms Salmonella spp, Escherichia Coli and Listeria Monocytogenes, on the inert surfaces of the Camal Municipal De Quevedo where the animals are fished for subsequent transfer to the markets of the city and sale to the consumer in which they can be introduced to human beings through meat and cause different diseases. The fieldwork was carried out in the Microbiology laboratory of the State Technical University of Quevedo, Campus "La María". The objective was to determine the presence or absence using the swab method and selective culture media (XLD, LISTERIA PALCAM, EMB LEVINE), sampling was performed on the floor, saw, ear hook, aerial hook, viscera hook and dispatch hook surfaces. The results obtained in UFC/cm2 on regular surface and Ufc/sampling surfaces on uneven surfaces, showed that oreo hook is within the established standard Peruvian Standard 461- Minsa with absence of Escherichia Coli and dispatch hook with absence of Listeria Monocytogenes; the other surfaces have a high microbial load on all other surfaces and the regular floor surfaces analyzed in comparison indicate that it is within the range in Absence of Salmonella spp, while Escherichia Coli and Listeria Monocytogenes are outside the range of the established standard. Keywords: UFC, Salmonella spp, Escherichia Coli and Listeria Monocytogenes, swab, inert surfaces.